Optimalisasi Dinamika Kelompok dalam Pendidikan dan Pelatihan: Strategi Peningkatan Kinerja Peserta di Lingkungan Pesantren - Abidin, Zainal; Rosid, Fathor (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This research aims to analyze group dynamics in the training context by focusing on four main aspects: group characteristics in training activities, stages of group development, encouragement and motivation of participants, as well as changes in performance and learning patterns of training participants. Using the library research method, this research examines various primary and secondary literature sources that are relevant to the theme of group dynamics among training participants. The research results show that the characteristics of groups in training include six important aspects: members' thoughts and cognition, motivation and expectations, group goals, organizational forum, relationships between individuals, and interaction and communication. The stages of group development include formation, conflict, implementation, evaluation and consolidation. The encouragement and motivation of training participants is influenced by their desire to learn, needs and hopes for the future. Changes in participant performance can be measured through three indicators: reaction, level of learning, and level of change in behavior after training. This research concludes that the success of training is marked by significant changes in the performance and abilities of participants as the main target for implementing training.